1965
DOI: 10.1139/v65-310
|View full text |Cite
|
Sign up to set email alerts
|

The Acid Hydrolysis of Glycosides: Ii. Effect of Substituents at C-5

Abstract: First-order rate coefficients a t three temperatures, and energies and entropies of activation, have been determined for the acid-catalyzed hydrolysis of methyl glucopyranosides containing various substituents a t C-5 and for glycopyranosiduronic acids with different aglycones. Substitution a t C-5 increased the stability towards acids of methyl a-and P-D-glucopyranosides, but there was no correlation between either the polarity or the size of the substituent and the rates of hydrolysis. The operation of eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

1967
1967
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(17 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The apparent activation energy found by Saeman was 179 kJ mol À1 . [67][68][69][70][71] Hiosawa et al reported that mercerized cotton cellulose oxidized with 2,2,6,6tetramethylpiperidine-1-oxyl (TEMPO) shows enhanced reactivity. [62] The presence of crystalline and amorphous domains has a strong determining effect on the reaction kinetics.…”
Section: Mechanism Of Acid-catalyzed Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent activation energy found by Saeman was 179 kJ mol À1 . [67][68][69][70][71] Hiosawa et al reported that mercerized cotton cellulose oxidized with 2,2,6,6tetramethylpiperidine-1-oxyl (TEMPO) shows enhanced reactivity. [62] The presence of crystalline and amorphous domains has a strong determining effect on the reaction kinetics.…”
Section: Mechanism Of Acid-catalyzed Hydrolysismentioning
confidence: 99%
“…On the other hand, the presence of oxidized groups, such as carboxylic, ketonic and aldehydic groups, was already investigated and reasonable evidence for their impact on the rate of hydrolysis has been provided by several authors. [67][68][69][70][71] Hiosawa et al reported that mercerized cotton cellulose oxidized with 2,2,6,6tetramethylpiperidine-1-oxyl (TEMPO) shows enhanced reactivity. [72] They found a linear correlation between the rate of hydrolysis and the content of carboxyl groups in the oxidized cellulose sample.…”
Section: Mechanism Of Acid-catalyzed Hydrolysismentioning
confidence: 99%
“…The rates of anomerisation described herein have the order glucopyranosiduronic acid > ester of glucopyranosiduronic acid > glucopyranoside, again demonstrating the role that a carboxylic acid group (and even a carboxylate ester) has in enhancing the catalytic efficiency of SnCl 4 . There are cases in which the rates of acid-catalysed hydrolysis of some b-d-glucopyranosiduronic acid derivatives are faster than corresponding b-d-glucopyranosides, [23] the hydrolysis of cyclohexyl b-d-glucopyranosiduronic acid being about five times faster than cyclohexyl b-d-glucopyranoside at 60 8C, for example. This trend is apparent herein, as the anomerisation of 20 b is faster than of 17 b.…”
Section: Resultsmentioning
confidence: 99%
“…The rates of hydrolysis of b-d-glucopyranosiduronic acids also depends on the electron affinity of the aglycon, [23] the hydrolysis of the cyclohexyl b-d-glucopyranosiduronic acid being approximately 30 times faster than that of the corresponding phenyl glycoside, for example. These rates also correlate with anomerisations, which were faster for cyclohexyl glycoside 20 b than for the phenyl glycoside 20 c. Timell and coworkers suggest that glucopyranosiduronic acids [23] are hydrolysed by a different mechanism to glucopyranosides [24] and it has been proposed that intramolecular general acid catalysis [25] through C 1 ÀO 1 bond cleavage (exocyclic cleavage) accounts for the rate enhancement observed for some glucuronic acid derivatives. This could involve an intermediate that adopts a 2 S O conformation (29), which would give an oxycarbenium ion (30) with a 2,5 B conformation [26] (Scheme 6, pathway a), or involve an intermediate that adopts a 1 C 4 conformation (31) giving an oxycarbenium ion with a half chair conformation (32; Scheme 6, pathway b).…”
Section: Resultsmentioning
confidence: 99%
“…No quantitative studies of this nature have been reported, except for the rather special case of the 2-amino group (19), which is protonated in acid solution. Previous studies of glycopyranoside hydrolysis concentrated on evaluating the effect of changes in structure of the aglycone (6,7,20,21),2 on varying substituents a t C-5 (8,22), and on changes in the sugar configuration and conformation (1, 6, 9).…”
mentioning
confidence: 99%